Roles of Autophagy Induced by Natural Compounds in Prostate Cancer. (3rd March 2015) - Naponelli, V.; Modernelli, A.; Bettuzzi, S.; Rizzi, F.
Abstract : Autophagy is a homeostatic mechanism through which intracellular organelles and proteins are degraded and recycled in response to increased metabolic demand or stress. Autophagy dysfunction is often associated with many diseases, including cancer. Because of its role in tumorigenesis, autophagy can represent a new therapeutic target for cancer treatment. Prostate cancer (PCa) is one of the most common cancers in aged men. The evidence on alterations of autophagy related genes and/or protein levels in PCa cells suggests a potential implication of autophagy in PCa onset and progression. The use of natural compounds, characterized by low toxicity to normal tissue associated with specific anticancer effects at physiological levels in vivo, is receiving increasing attention for prevention and/or treatment of PCa. Understanding the mechanism of action of these compounds could be crucial for the development of new therapeutic or chemopreventive options. In this review we focus on the current evidence showing the capacity of natural compounds to exert their action through autophagy modulation in PCa cells.